PENYULUHAN TENTANG PEMBANGUNAN SEPTIC TANK DAN SANITASI YANG BAIK - Meylida, Dhonna; Arum Dwicahyani; Ahmad Hidayawan; Andri Kurniawan; Bagas Wahyu Adhi; Farhan Febrian (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The community service activity was carried out in Handil Maluka Village with the aim of increasing public awareness of the importance of proper sanitation and household waste management. This activity was conducted due to the community’s limited knowledge about proper sanitation, particularly regarding the crucial role of septic tanks and waste management. The methods implemented included counseling sessions, interactive discussions, and continuous monitoring after the outreach activities. The program was conducted alongside the construction of 50 septic tanks and free toilets in Handil Maluka Village. The results of the outreach activities showed an improvement in community hygiene practices, such as the establishment of waste disposal points in several areas and the implementation of better waste management. During the current rainy season, no flooding occurred, which had previously been an annual issue for the community. This activity successfully fostered community awareness of the importance of proper sanitation.